IMPLIKASI PENERAPAN PARENTING TERHADAP KEHARMONISAN KELUARGA: STUDI KASUS PADA JEMAAH KAJIAN MASJID IMAM ASY-SYAFI’I DEPOK - Mohamad Adam Mahmudin; Syafiq Riza Hasan (USRAH: Jurnal Hukum Keluarga Islam, 2026)
Parenting refers to the  attitudes, behaviors, and caregiving strategies implemented by parents toward their children. It is a dynamic process subject to change according to the era’s development and the family environment, which plays a vital role in shaping a child’s character and behavior. A lack of parental attention is occasionally caused by work-related busyness, social environmental influences, and a limited understanding of parenting, thereby constraining quality time with the children. This situation is also experienced by  the congregation members of the Imam Asy-Syafi'i Mosque study group in Depok. The study aims to analyze and describe the level of family harmony, the types of parenting styles implemented, the supporting and inhibiting factors, and the Islamic values applied by the congregation members. This research employed a qualitative approach with a case study design, utilizing in-depth interviews and participatory observation. The findings indicate that family harmony is characterized by three primary indicators: fulfilling rights and responsibilities, open communication and positive conflict resolution, and comfort in performing worship and adherence to rules. Furthermore, the applied parentin include democratic, authoritarian, and a combination of the two. Supporting factors encompass spousal support, continuous learning, consistency in implementing rules, and a positive educational and social environment. Conversely, inhibiting factors include a lack of knowledge and patience, inconsistency, and rejection from the child. The Islamic values implemented to enhance family harmony are the early inculcation of Tawhid (monotheism), regular reading of the Qur'an, active participation in religious studies, and providing a good role model.